Predicting the outcome of adductor tenotomy - Cottalorda, J. (Springer-Verlag, 1998)
This study reviewed 57 hips in 30 children (18 girls and 12 boys) with cerebral palsy who had undergone an adductor tenotomy alone or in combination with an anterior obturator neurectomy (23 hips). Results were evaluated by the Reimers migration percentage (MP). The hips were split into three groups: group A (12 hips) a preoperative MP of less than 20%, group B (25 hips) between 20 and 40%, and group C (20 hips) more than 40%. The mean age at the time of surgery was 6 years and 1 month (range: 2.5–13 years). The mean period of review was 6 years and 3 months (2–20 years). The results were considered as ”good” when radiographs at the longest follow-up showed a decrease of >10% of the MP, as ”bad” when they showed an increase of >10%, and as ”stable” when the MPs varied less than 10%. At the latest review of group A, 11 were stable (92%) and 1 was bad. In group B, 12 were stable (48%), 7 were good (28%), and 6 were bad (24%). In group C, 7 were stable (35%), and 13 were bad (65%). The preoperative migration percentage proved to be the only predictor of outcome. Age at the time of surgery had no constant significant effect on the outcome, neither had the addition of an anterior neurectomy.